On Testing Significance of the Multivariate Rank Correlation Coefficient - Kończak, Grzegorz (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The Spearman’s rho is a measure of the strength of the association between two variables. There are some extensions of this coefficient for the multivariate case. Measures of the multivariate association which are the generalisation of the bivariate Spearman’s rho are considered in the literature. These measures are based on copula functions. This article presents a proposal of the testing for the multivariate Spearman’s rank correlation coefficient. The proposed test is based on the permutation method. The test statistic used in the permutation test is based on the empirical copula function. The properties of the proposed method have been described using computer simulations.